PENTANAAN JARINGAN TRAYEK ANGKUTAN PERKOTAAN DI KOTA BOGOR: ESTABLISHMENT OF URBAN TRANSPORT TRACK NETWORK IN BOGOR CITY - Althafurrahman; Sri Yuniarti (FTSP Universitas Jayabaya, 2021)
Bogor city is mostly occupied by public transport. Nowadays, the number of routes of public transport routes in Bogor city is 24 routes. However, in the implementation there are mostly routes of public transport that are overlapping. This study is doing because the overlapping of routes of public transport is beyond 50% and it made the load factor in each route become low. The method that I did was collecting data with dynamic survey and static survey for anlalyzing the real condition of public transport routes and other data like interviews, Home Interview, and Road Side Interview for predicting the demand of trips that are processed in VISUM app to get the demand of trips on each road as a basis to make new suggestion routes for public transport. The last step is to analyze and to compare the real routes and the suggestion routes. Both performance of routes and performance of operational. After all of those analyses we only need 14 routes of public transport, so it is expected to increase the load factor of public transport by 70%